Antibody responses to inactivated SARS‐CoV‐2 vaccine in peritoneal dialysis patients. Issue 3 (6th January 2022) - Murt, Ahmet; Altiparmak, Mehmet R.; Ozbey, Dogukan; Yalin, Serkan F.; Sert Yadigar, Serap; Karaali, Ridvan; Kocazeybek, Bekir; Saltoglu, Nese; Pekpak, Meltem; Ataman, Muveddet R.
Abstract: Introduction: As end‐stage renal disease (ESRD) patients generally have reduced responses to the vaccines, effectiveness of newly developed SARS‐CoV‐2 vaccines in ESRD are also matters of curiosity. We aimed to investigate the humoral responses of our peritoneal dialysis (PD) patients to the inactivated SARS‐CoV‐2 vaccine. Methods: Humoral immune responses of 23 PD patients who received two doses of the inactivated SARS‐CoV‐2 vaccine were investigated with a commercial test that measures IgG antibodies towards receptor binding domain of SARS‐CoV‐2 spike protein. Seropositivity rates, antibody titers, and ESRD related clinical data were compared with 51 hemodialysis (HD) patients and 29 healthy volunteers. Results: Seropositivity of PD patients with the inactivated vaccine was 95.6%. Both the rate of seropositivity and SARS‐CoV‐2 IgG antibody levels in PD patients were not different from the healthy controls ( p = 0.85 and 0.19, respectively). While seropositivity rates were not different for PD or HD patients ( p = 0.09), the magnitude of humoral responses was significantly higher in PD patients ( p = 0.0001). There were no vaccine‐related serious adverse events. In the 3‐months clinical follow‐up, none of the patients experienced SARS‐CoV‐2 infection. Conclusion: Two doses of the inactivated vaccine generate adequate humoral immune response in PD patients without any serious adverse events.